2020
DOI: 10.3390/metabo10110436
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Study of Serum from a Chronic Alcohol-Fed Rat Model Following Administration of Defatted Tenebrio molitor Larva Fermentation Extract

Abstract: We have previously showed that defatted mealworm fermentation extract (MWF) attenuates alcoholic liver injury by regulating lipid, inflammatory, and antioxidant metabolism in chronic alcohol-fed rats. The current metabolomics study was performed to monitor biochemical events following the administration of MWF (daily for eight weeks) to a rat model of alcoholic liver injury by gas chromatography-tandem mass spectrometry (GC-MS/MS). The levels of 15 amino acids (AAs), 17 organic acids (OAs), and 19 free fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…As regards the insects, 35 different species were investigated; the ones that arouse major interest in researchers were T. molitor and those belonging to the Gryllydae family, respectively studied in 13 and 10 different researches. However, it is interesting to note that the experimental studies carried out in vivo are mainly focused on G. bimaculatus, P. brevitaris, and B. mori, while curiously, all the studies performed using T. molitor are in vitro, with only one exception (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As regards the insects, 35 different species were investigated; the ones that arouse major interest in researchers were T. molitor and those belonging to the Gryllydae family, respectively studied in 13 and 10 different researches. However, it is interesting to note that the experimental studies carried out in vivo are mainly focused on G. bimaculatus, P. brevitaris, and B. mori, while curiously, all the studies performed using T. molitor are in vitro, with only one exception (35).…”
Section: Discussionmentioning
confidence: 99%
“…The ethanolic extracts of Protaetia brevitaris larvae, administered with a high-fat diet for 7 weeks, increased GPx and CAT in liver of obese C57BL/6J mice (34). Finally, the treatment fermented defatted T. molitor powder of Sprague-Dawley rats fed with a chronic alcohol diet dose-dependently increased hepatic β-oxidation (35).…”
Section: Antioxidant Activity Of Edible Insects In Cells and Animal Mmentioning
confidence: 94%
See 1 more Smart Citation
“…Abnormal regulation of FAs has been frequently reported in cardiovascular diseases such as myocardial infarction and hypertrophy [ 6 ]. Studies of serum metabolomics have also demonstrated that free fatty acids can damage biological membranes and are partly responsible for the functional and morphological changes of alcohol-induced diseases [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of twenty-five intervention studies in animal models and two in humans have been published, as described in Table 6. Fifteen different edible insects were investigated: five papers involved Gryllus bimaculatus (6,45,47,51,52) and four Tenebrio molitor (39,48,53,54) , while the use of Oxya chinensis sinuosa (37,47,55) and Protaetia brevitaris seulensis (38,47,49) was reported in three interventions each. One study investigated the effects of both acute and chronic settings, while four were only acute (i.e.…”
Section: Effect Of Edible Insects In Animal and Human Studiesmentioning
confidence: 99%